Human Factors in Privacy Research - Gerber, Nina; Stöver, Alina; Marky, Karola (Springer Nature, 2023)
This book covers topics needed to be considered in research around usable privacy. The book starts from a psychological perspective and introduces readers to basic behavioral theories and models that can explain end-user privacy behavior (including the "privacy paradox") on a theoretical level. Subsequently, an introduction to different study methods (e.g., experiment, survey, interviews, co-creation) used in usable privacy research is given. Based on this, different methodological aspects, such as identifying appropriate questionnaires, and applying User-Centered Design, will be discussed. Finally, the book describes application areas for privacy research such as dark patterns and presents solutions for privacy protection, e.g., regarding consent-giving and PETs. The book aims to bring together the different research approaches to the topic of usable privacy, which often originate from computer science, psychology, and law, and provide a methodologically sound basis for researchers who want to delve deeper into this topic. This is an open access book.